A step toward autonomy in education: probing into the effects of practicing self-assessment, resilience, and creativity in task supported language learning - Mubarak S. Aldosari; Haroon N. Alsager (BMC Psychology, 2023)
Abstract Self-assessment (SA) can provide students with opportunities to self-evaluate, or make judgments about their learning process and products of learning. Regarding the importance of SA, this survey pursued to examine the effects of practicing SA on Saudi Arabian EFL learners’ resilience, creativity, and autonomy in task supported language learning. To fulfill these objectives, 60 intermediate EFL learners were chosen and separated accidentally into two groups of control and experimental. They were then pre-tested using three related questionnaires of resilience, creativity, and autonomy. Next, the treatment was practiced on the two groups. Eight lessons of Touchstone Book 3 were taught to the experimental group using SAvia applying different tasks. On the other hand, the lessons were trained to the control group without using SA and tasks. The aforementioned questionnaires were re-administered as the post-tests following the completion of all lessons. Independent and paired samples t-test findings displayed that the control and experimental groups performed differently on the three post-tests. In essence, the results showed that the experimental group's resilience, creativity, and autonomy were all improved by the treatment. The research's implications and conclusions were then outlined. The implications of the research can allow students to evaluate their own progress and skill development critically.